Iron oxide nanoparticles and VOx/Hexadecylamine nanotubes composite - Saleta, Martin Eduardo (2008)
In this work, we present the synthesis and characterization of a hybrid nanocomposite constituted by iron oxide nanoparticles and vanadium oxide/Hexadecylamine (VOx/Hexa) nanotubes. Transmission Electron Microscopy (TEM) images show small particles (around 20 nm) in contact with the external wall of the multiwall tubes, which consist of alternate layers of VOx and Hexa. By Energy Dispersive Spectroscopy (EDS), we detected iron ions within the tube walls and we have also established that the nanoparticles are composed of segregated iron oxide. The samples were studied by Electron Paramagnetic Resonances (EPR) and dc-magnetization as a function of the magnetic field. The analysis of the magnetization and EPR data confirms that a fraction of the V atoms are in the V4+ electronic state and that the nanoparticles exhibit a superparamagnetic behavior. The percentage of V and Fe present in the nanocomposite was determined using Instrumental Neutron Activation Analysis (INAA).